Impact of Reconstructing Intercostal Artery on Spinal Cord Circulation During Open Surgery for Thoracoabdominal Aortic Aneurysm - Kobayashi,Kei (2022)
ABSTRACT Introduction: We evaluated the outcomes of the selective intercostal artery reconstruction for preventing spinal cord injury during thoracoabdominal aortic aneurysm repair. Methods: We retrospectively assessed 84 consecutive patients who underwent thoracoabdominal aortic aneurysm repairs between 2004 and 2016. The mean age of the patients was 57.3 years. We performed preoperative multidetector computed tomography in 74 patients (88.0%) to identify the Adamkiewicz artery. Spinal cord injury preventive measures included motor evoked potential monitoring, hypothermia induction, Adamkiewicz artery or other intercostal artery reconstruction, and cerebrospinal fluid drainage. Results: The hospital death rate was 5.9%, and paraplegia occurred in four patients (4.7%). The Adamkiewicz artery or other intercostal arteries were reconstructed selectively in 46 patients (54.7%). Of these patients, 41 underwent postoperative multidetector computed tomography, which revealed occlusion of the reconstructed grafts in 23 patients (56.0%). There was no paraplegia in the patients who underwent reconstruction of the Adamkiewicz artery, which was patent on postoperative multidetector computed tomography. Univariate analysis showed no significant effect of various risk factors on the development of spinal cord injury. Conclusion: Outcome of open surgery for thoracoabdominal aortic aneurysm in our institution regarding spinal cord injury was satisfactory. The benefits of Adamkiewicz artery reconstruction remain inconclusive, and further larger studies are required to identify its validation for spinal cord protection in thoracoabdominal aortic aneurysm repair.